Harmonizing Copyright in the EU's Digital Single Market: Benefits and Barriers - Damayanti, Fitria; Zacky, Muhammad Farid; Soeparna, Intan (Universitas Internasional Batam, 2024)
The rapid advancement of digital technology has reshaped global trade and commerce, particularly in the European Union (EU), where the Digital Single Market (DSM) strategy seeks to create an integrated online economy across member states. This research examines the intersection of the DSM and Intellectual Property Rights (IPR), particularly focusing on copyright protection in the digital space. The EU’s efforts to eliminate cross-border barriers, enhance e-commerce, and foster innovation have profound implications for copyright law, highlighting both opportunities and challenges for creators and businesses. Through the introduction of the EU Copyright Directive (Directive 2019/790), the EU aims to modernize copyright rules, offering greater legal certainty and protection for digital content creators. However, the digital economy also brings challenges such as geo-blocking, territorial licensing, and issues related to piracy, which hinder seamless access to digital content across borders. This study explores the benefits and obstacles of the DSM strategy in relation to IPR, providing insights into the complexities of balancing copyright protection with the need for an open and integrated digital market.